Ozone therapy, a supplement for patients with fibromyalgia (Ozone Therapy Global Journal, 2014)
Fibromyalgia is a disease of unknown ca use whose main sym ptom is chronicwidesprea d musculos keletal pain accompanied by s ymptoms th at disrupt dailyactivities of patients. In this study the impact of ozone therapy in improving patients'pai n and daily ac tivities to give them a bet ter quality of life was assessed. Clinicalexperience is described us i ng ozone t herapy in 30 wo me n aged 30 -65 yearsdiagnosed with Fibromyalgia, Visual Analogue Scale (VAS) 6-9, with a time of diseaseprogression between 1-10 years. Patients were treated with O2-O3 intramuscular with10 sessions 2 times a week at doses o f 15 mg / mL, to gether were administeredsystemically 10 sessions 2 times a week alternating rectal insufflation and intravenousadmi nistration of s aline 0.9% ozonated. The outcome of patients was continued bymonitoring clinical symptoms and evaluation of the Visual Analogue Scale.The results showed an improvement in pain with 33% VAS 3-4 in the second week,improved sleep disorder in 46.6%, mood and daily activities by 40% and appreciateda decrease in the amount of drugs consumed by 30% of patients.The ozone therapy can be considered as an interesting as adjuva nt ther apy in thesymptoms of fibromyalgia.